Activation of lateral parabrachial afferent pathways and endocrine responses during sodium appetite regulation - Godino, Maria Andrea del Milagro (2010)
Modulation of salt appetite involves interactions between the circumventricular organs (CVOs) receptive areas and inhibitory hindbrain serotonergic circuits. Recent studies provide support to the idea that the serotonin action in the lateral parabrachial nucleus (LPBN) plays an important inhibitory role in the modulation of sodium appetite. The aim of the present work was to identify the specific groups of neurons projecting to the LPBN that are activated in the course of sodium appetite regulation, and to analyze the associated endocrine response, specifically oxytocin (OT) and atrial natriuretic peptide (ANP) plasma release, since both hormones have been implicated in the regulatory response to fluid reestablishment. For this purpose we combined the detection of a retrograde transported dye, Fluorogold (FG) injected into the LPBN with the analysis of the Fos immunocytochemistry brain pattern after sodium intake induced by sodium depletion. We analyzed the Fos-FG immunoreactivity after sodium ingestion induced by peritoneal dialysis (PD). We also determined OT and ANP plasma concentration by radioimmunoassay (RIE) before and after sodium intake stimulated by PD. The present study identifies specific groups of neurons along the paraventricular nucleus, central extended amygdala, insular cortex, dorsal raphe nucleus, nucleus of the solitary tract and the CVOs that are activated during the modulation of sodium appetite and have direct connections with the LPBN. It also shows that OT and ANP are released during the course of sodium satiety and fluid reestablishment. The result of this brain network activity may enable appropriate responses that re-establish the body fluid balance after induced sodium consumption. © 2009 Elsevier Inc. All rights reserved.